2015
DOI: 10.1111/obr.12308
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease as a consequence of autonomic imbalance and circadian desynchronization

Abstract: The circadian system, headed by the suprachiasmatic nucleus, synchronizes behaviour and metabolism according to the external light-dark cycle through neuroendocrine and autonomic signals. Metabolic diseases, such as steatosis, obesity and glucose intolerance, have been associated with conditions of circadian misalignment wherein the feeding schedule has been moved to the resting phase. Here we describe the physiological processes involved in liver lipid accumulation and show how they follow a circadian pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 161 publications
(205 reference statements)
1
28
0
1
Order By: Relevance
“…Studies have demonstrated that patients with NAFLD had a higher prevalence of autonomic disturbance. [ 38 39 40 ] The cause of this increased autonomic abnormality is still not known. Studies have also shown that autonomic dysfunction could lead to abnormal gastric and esophageal motility and, thus, predispose to development of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that patients with NAFLD had a higher prevalence of autonomic disturbance. [ 38 39 40 ] The cause of this increased autonomic abnormality is still not known. Studies have also shown that autonomic dysfunction could lead to abnormal gastric and esophageal motility and, thus, predispose to development of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Evolving information suggests that the incidence and mortality of HCC are expected to rise since the increasingly metabolic syndrome with NAFLD, in addition to viral hepatitis and alcohol-induced liver diseases [ 130 ]. In view of the link between disrupted circadian rhythms and NAFLD has been extensively investigated [ 132 , 133 ], it is of interest to explore the functions and mechanisms of circadian clock involved in HCC.…”
Section: Circadian Rhythms In Liver Cancermentioning
confidence: 99%
“…Amount evidence revealed that late sleep timing could lead to a disruption of circadian rhythm . On the one hand, circadian misalignment induced an unbalanced activity of the sympathetic‐parasympathetic branches between organs that contributed to the accumulation of fat in the liver . On the other hand, an experimental study demonstrated that circadian misalignment disrupted the liver clock and induced a global metabolic dysfunction in liver .…”
Section: Introductionmentioning
confidence: 99%